1965
DOI: 10.4141/cjps65-065
|View full text |Cite
|
Sign up to set email alerts
|

The in Vitro Digestibility and Protein Content of Leaf and Stem Portions of Forages

Abstract: The in vitro dry matter digestibility'(I.V.D.) of the immaure stems of timothy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 7 publications
9
61
1
Order By: Relevance
“…These results agree with those of Terry and Tilley (1964) and Mowat et al (1965) on in vitro digestibility of dry matter, and with those of Sanderson and Wedin (1989) on in vitro digestibility and NDF concentration. The results of Mowat et al (1965) also indicated that the digestibilities of both leaves and stems of earlymaturing cultivars on a given date were less than those of late-maturing cultivars. Our results, however, indicate no differences in IVTD, IVCWD, and NDF concentrations of leaves between the early and late-maturing cultivars used in this study.…”
Section: Results and Discussion Relationship Of Nutritive Value With supporting
confidence: 82%
See 1 more Smart Citation
“…These results agree with those of Terry and Tilley (1964) and Mowat et al (1965) on in vitro digestibility of dry matter, and with those of Sanderson and Wedin (1989) on in vitro digestibility and NDF concentration. The results of Mowat et al (1965) also indicated that the digestibilities of both leaves and stems of earlymaturing cultivars on a given date were less than those of late-maturing cultivars. Our results, however, indicate no differences in IVTD, IVCWD, and NDF concentrations of leaves between the early and late-maturing cultivars used in this study.…”
Section: Results and Discussion Relationship Of Nutritive Value With supporting
confidence: 82%
“…On a given date during primary growth, early-maturing timothy cultivars are generally more advanced in phenological development and are less digestible than late-maturing cultivars (Mowat et al 1965;Kunelius 1990). Bélanger and McQueen (1996) also showed that when compared with late-maturing cultivars of timothy on a given date, earlymaturing cultivars had lower in vitro true digestibilities of dry matter and cell wall, and greater NDF concentrations.…”
Section: Mot Clésmentioning
confidence: 99%
“…This agrees with Mowat et al (1965) and Nelson and Moser (1994). By the end of the regrowth corresponding to a normal harvesting date at the For personal use only.…”
Section: Seasonal Effectsupporting
confidence: 82%
“…This supports the findings from several studies (Buxton and Casler 1993). Contrary to our speculation in a previous paper (Bélanger and McQueen 1998) and to results reported by Terry and Tilley (1964) and Mowat et al (1965), the present results indicate that the nutritive value of leaf blades in spring was greater than that of sheaths at the early vegetative stage (Tables 2 and 3).…”
Section: Seasonal Effectcontrasting
confidence: 57%
“…Mots clés: Poa pratensis L., qualité fourragère, graminée vivace, feuille, tige Herbage quality of cool-season grasses declines with advancing maturation. Herbage digestibility and CP concentration decrease, whereas fiber and lignin concentrations increase with maturation (Pritchard et al 1963;Mowat et al 1965). The decline in whole herbage quality of smooth bromegrass (Bromus inermis Leyss) with maturation was attributed to a decrease in the leaf/stem mass ratio as well as to changes in the quality of leaf and stem fractions.…”
mentioning
confidence: 99%